Актуальні проблеми та напрямки вдосконалення системи протидії корупції у публічній службі - Музичук, Е. О.; Muzychuk, E. O.; Едуард Музичук (Форум права. - 2023. - № 3(76). - С. 79-86, 2023)
Визначено актуальні проблеми і напрямки вдосконалення системи протидії корупції у публічній службі. Показано, що оптимізація системи суб’єктів, які беруть участь у протидії корупції в публічній службі, потребує реалізації конкретних напрямків вдосконалення. Ці заходи спрямовані на досягнення таких важливих цілей, як зменшення рівня корупції та підвищення прозорості та ефективності у функціонуванні публічної служби взагалі. До цих напрямків вдосконалення відносяться поліпшення законодавчої бази, впровадження ефективного механізму міжвідомчої співпраці і координації, а також активне залучення громадськості до процесу протидії корупції. Здійснення цих заходів може суттєво сприяти покращенню боротьби з корупцією в публічній службі та забезпечити більш прозорий та ефективний функціонування державних органів.

Ukraine faces a significant issue of corruption in the public service sector, which has resulted in detrimental consequences for society, the efficiency of government administration, and citizens' trust in the authorities. Currently, the problems in the anti-corruption system within the public service sector encompass insufficient authority and resources for anti-corruption agencies, ineffective coordination among anti-corruption entities, frequent legislative changes, and inadequate oversight and involvement of the public in monitoring and controlling governmental processes. These challenges create substantial obstacles to the establishment of an efficient and transparent anti-corruption system within the public service. Therefore, there is a need for research to identify the current issues and determine directions for further improvement of this system to achieve high standards of integrity and effectiveness in the Ukrainian public service. The purpose of this article is to identify current issues and directions for enhancing the anti-corruption system within the public service. Legal expertise methods were employed to assess and analyze specific legislative acts and their alignment with anti-corruption principles, as well as diagnostic analysis to identify key issues and shortcomings in the anti-corruption system. Results. It has been demonstrated that optimizing the system of entities involved in combating corruption in the public service requires the implementation of specific areas of improvement. These measures are aimed at achieving critical objectives, such as reducing the level of corruption and enhancing transparency and efficiency in the overall functioning of the public service. These areas of improvement encompass enhancing the legislative framework, introducing an effective mechanism for interagency cooperation and coordination, as well as actively engaging the public in the fight against corruption. Implementing these measures can significantly contribute to improving the anti-corruption efforts within the public service and ensuring a more transparent and efficient operation of government institutions. Conclusions. Among the crucial measures aimed at enhancing the anti-corruption system within the public service, several stand out, including the development and implementation of effective control systems over property and income declarations of officials, the utilization of blockchain technology in public procurement, active engagement of the public in combating corruption, improvements in control mechanisms within the public service, the implementation of software solutions for more effective anti-corruption measures, fostering cooperation between anti-corruption bodies and international organizations, strengthening the independence and effectiveness of the judicial system, harnessing modern information technologies, and promoting further economic development of the country.

Определены актуальные проблемы и направления усовершенствования системы противодействия коррупции в публичной службе. Показано, что оптимизация системы субъектов, участвующих в противодействии коррупции в публичной службе требует реализации конкретных направлений совершенствования.
Actual problems and directions for improvement of the anti-corruption system in the public service
Keywords: протидія корупції; система протидії корупції; оптимізація; публічна служба; правове регулювання; державна політика; законодавче забезпечення; адміністративне право; anti-corruption; anti-corruption system; optimization; public service; legal regulation; state policy; legislative support; administrative law; противодействие коррупции; система противодействия коррупции; оптимизация; публичная служба; правовое регулирование; государственная политика; законодательное обеспечение; административное право